ENVIRONMENTAL COMMUNICATION THROUGH EDUCATIONAL SOCIALIZATION WASTE RECYCLING BY SAMPAH BERSINAR BANK BANDUNG WEST JAVA INDONESIA - Surya, Desayu Eka; Andini, Siti Sri (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
The aim of the research is to study environmental communication through the socialization of waste recycling education by the Bersinar Sampah Bank in managing household waste in West Java. Qualitative research method: descriptive study. The research results show that the principles used are Reduce, Reuse and Recycle. A strategy is formulated, by determining the location of the socialization point, trying to get an invitation to participate in the socialization. Using a persuasive approach to influential figures, being involved in community activities, selling the benefits of waste disposal activities. The communication technique used is persuasive communication, trying to change people’s mindsets and attitudes towards disposing of and managing household waste. The research conclusion is that environmental communication through socialization and education on waste recycling has been effective and efficient, with the construction of hundreds of waste bank units, with thousands of customers spread throughout West Java.